Obscure-occult bleeding: resolution of unexplained chronic sideropenic anaemia by colonoscopic removal of a colonic leiomyoma. (2nd February 2011) - Urgesi, Riccardo; Pastorelli, Alfredo; Zampaletta, Costantino; Masini, Andrea; Pelecca, Giorgio; Faggiani, Roberto; Anti, Marcello
Abstract : Although leiomyomas of the stomach or small intestine are relatively common, those of the colon or rectum are rare. Several cases of endoscopic resection of colorectal leiomyomas have been described. However, conventional polypectomy of leiomyomas can result in perforation. To reduce the risk of perforation, submucosal injection can be performed before removal. We report a case of chronic sideropenic anaemia in a patient affected by leiomyoma of the sigmoid colon in which after complete endoscopic enucleation of the lesion we obtained the stable resolution of anaemia.